2014
DOI: 10.15517/rbt.v62i4.12844
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological responses of seagrasses (Alismatales) to grazers (Testudines: Cheloniidae) and the role of these responses as grazing patch abandonment cues

Abstract: Green sea turtles, Chelonia mydas, are grazers influencing the distribution of seagrass within shallow coastal ecosystems, yet the drivers behind C. mydas patch use within seagrass beds are largely unknown. Current theories center on food quality (nutrient content) as the plant responds to grazing disturbances; however, no study has monitored these parameters in a natural setting without grazer manipulation. To determine the morphological and physiological responses potentially influencing seagrass recovery fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
2
10
1
Order By: Relevance
“…The paradigm about N depletion in tissues as a patch abandonment cue is not supported by our data nor to those reported in previous studies (Moran & Bjorndal 2007;Fourqurean et al 2010). Turtles most likely stopped grazing because not much new tissue was formed, as shoot density decreased (this study) or the leaves stopped growing as suggested by Lacey, et al (2014), which was likely driven by the decline in soluble carbohydrates content (table 4, Moran & Bjorndal 2007). Robust seagrass species like T.…”
Section: Changes In Thalassia Testudinum Under a Rotational Grazing Rcontrasting
confidence: 54%
See 2 more Smart Citations
“…The paradigm about N depletion in tissues as a patch abandonment cue is not supported by our data nor to those reported in previous studies (Moran & Bjorndal 2007;Fourqurean et al 2010). Turtles most likely stopped grazing because not much new tissue was formed, as shoot density decreased (this study) or the leaves stopped growing as suggested by Lacey, et al (2014), which was likely driven by the decline in soluble carbohydrates content (table 4, Moran & Bjorndal 2007). Robust seagrass species like T.…”
Section: Changes In Thalassia Testudinum Under a Rotational Grazing Rcontrasting
confidence: 54%
“…Rotational grazing by green turtles decreases the aboveground community biomass, particularly that of T. testudinum. Grazed patches are maintained for one to two years after they are abandoned most likely because of reduced leaf growth due to internal carbohydrate depletion; (Fourqurean et al 2010;Lacey et al 2014;), and the turtles do not return to abandoned patches (Molina-Hernández & van Tussenbroek 2014). Abandoned patches show thinner and shorter leaves of T. testudinum, with sparser seagrass shoots than ungrazed nearby meadows (Molina-Hernández & van Tussenbroek 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the effect persists for too long, the resources will be exhausted, as was demonstrated here. Thereby, the plants cannot compensate and instead have to adapt by reducing shoot density and total leaf area [54]. …”
Section: Discussionmentioning
confidence: 99%
“…Such an effect has previously been observed in T . testudinum [54] exposed to turtle and fish grazing, while a study of T . hemprichii found no effect of clipping on leaf width [52].…”
Section: Discussionmentioning
confidence: 99%